Analisis Kesiapan Belajar Siswa Kelas XII Madrasah Aliyah Negeri 1 Serang dalam Mengikuti Mata Pelajaran Matematika - Shevia Annisa; Heni Pujiastuti (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
This study aims to analyze the learning readiness of class XII students of MA Negeri 1 Serang in participating in mathematics lessons. The type of research used is descriptive qualitative research. This research was conducted in March – June 2021 with the subject of class XII students at MA Negeri 1 Serang. The sampling technique used is purposive sampling. Research instruments in the form of questionnaires, observations and interviews. The procedure for implementing the data includes the preparation stage, stages and stages of journal preparation. Data processing was carried out by analyzing the results of the student learning readiness questionnaire by calculating the suspension obtained and then describing it with a presentation according to the learning readiness category. The results showed that the readiness of class XII Madrasah Aliyah Negeri 1 Serang students was included in the sufficient category with an average percentage of 74.15%. The results of the research on the aspect of physical readiness obtained a percentage of 77.30%, psychological readiness of 76.11%, material readiness of 74.19% and cognitive readiness obtained the lowest score of 68.19%.